Perinatal outcome and associated factors of laboring mothers with admission cardiotcography admitted to Gonder University Hospital labor ward , North West Ethiopia 2021-2022 G.C. - gizaw, tsegaye (Ethiopian Journal of Reproductive Health, 2025)
Background: Admission CTG or labor admission test is a CTG of 20 minutes in duration done when a woman is admitted to labor ward. Worldwide more than 2.6 million stillbirths occur annually, one cause being birth asphyxia and among the methods proposed to reduce birth asphyxia one is using admission CTG. Objective: To describe perinatal outcome of laboring mothers with admission CTG, assess its predictive power for perinatal outcome and to assess associated factors. Methods: Prospective single center observational study was conducted among 385 laboring mothers with admission CTG admitted to GUH L/W . The data was coded & entered using Epi data version 4.6. Then the data was exported to STATA version 14 for cleaning and analysis. Descriptive, as well as bivariate statistical analysis was done using chi 2 test & p value< 0.05 considered statistically significant and were subject to multivariate analysis to identify independent factors associated with outcome variables. Results: Out of 385 laboring mothers with admission CTG 82% were having normal admission CTG,14% suspicious CTG & the remaining 4% pathologic admission CTG. Mothers with abnormal admission CTG were also having high rate of low APGAR score. Simillarlly NICU admissions, development of ominous or NRFHRP and development of MSL in labor were higher among the abnormal admission CTG groups. The Sn, Sp PPV, NPV & diagnostic accuracy of admission CTG for ominous or NRFHRP in labor were 42.9%,86%,34.2%,89.8% &79.7% for that of low APGAR score it was 75%,82.4%,4.3%,99.6% &82.3% simillarlly it was 23%,82.3%,15.7%,88.3% and 75% for NICU admission. The decision to delivery & pattern of admission CTG were independent factors associated with development of ominous or NRFHRP in labor. Conclusion: Admission CTG is specific screening test with good negative predictive value for detection of ominous or NRFHRP in labor, development of MSL in labor, predicting NICU admission and development of low APGAR score but with poor sensitivity and fair diagnostic accuracy. Pattern of admission CTG at time of admission needs a due emphasis.